IDENTIFICATION AND PROJECTION OF THE QUANTITY OF FOOD TO BE SUPPLIED TO MUNICIPAL INSTITUTION STUDENTS/ CUSTOMERS IN REZEKNE MUNICIPALITY - Zvaigzne, Anda; Kotāne, Inta; Klodāne, Aļona; Jackaničs, Andrejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Regardless of food market globalisation, in recent years a topical matter has been food consumption as close to the production site as possible or local food. Research studies conducted in the world and in Latvia too show that the introduction of green public procurement contributes to the development of a local area and directly promotes and ensures increases in local product sales, thereby stimulating the purchase of local food to supply customers and students of municipal institutions with food. The authors believe that a timely examination of the situation and a projection of the required amount of food for customers/students of municipal institutions are essential prerequisites for local enterprises in Rezekne municipality to plan and develop their businesses. The paper is based on the implementation results of the research grant "Opportunities for the Green Public Procurement of Food by Municipal Institutions in Rezekne Municipality”. The research aim is to identify and project the quantity of food to be supplied to municipal institution customers/students in Rezekne municipality. The research results indicate that the demand for food to be supplied through public procurement by Rezekne municipality municipal institutions might remain the same in the nearest future. Holding public food procurement tenders in future, the local authorities of Rezekne municipality have to split any large amount of procured food into smaller ones, thus giving an opportunity for local small enterprises to participate in the tenders. Research methods used: monographic, descriptive, analysis, synthesis, data grouping, statistical analysis and a sociological method – a survey of municipality/parish administration representatives.